POLA REPRODUKSI BEBERAPA JENIS CYPRINIDAE DI PERAIRAN LEBAK LEBUNG, LUBUK LAMPAN, SUMATERA SELATAN - D.I. HARTOTO; SULASTRI SULASTRI; I. RACHMATIKA (BERITA BIOLOGI, 1985)
D.I. HARTOTO, SULASTRI & I. RACHMATIKA. 1985. Reproductive pattern of some Cyprinids species at Lebak Lebung flood plain area,Lubuk Lampan, South Sumatera. Berita Biologi 3(3): 128 - 135. -A study on reproductive characteristics of three Cyprinids species was conducted in Lubuk Lumpam; a floodplain area in South Sumatera during the early rainy season of 1981. A study of fecundity supported by other biological aspects was used as an approach to reveal the reproductive pattern. Analysis of the Osteochilus hasselti showed that the fish was an early and multiple spawner that strats to breed in a submerged vegetation habitat type before the peak of food abundance in the rainy season. All of the species could not be grouped as small brood spawners, including the least fecund fish Rasbora lateristriata that spawns late in its life span. Chela oxygasteroides showed a similar pattern to the two other species except that it was predicted to spawn during the time of food abundance. Based on Horn's diagram, recapitulation analysis on factors of reproductive strategy indicated that three Cyprinids could be grouped as r - strategist.